Gender diversity in boardrooms – A literature review - Sudheer Reddy; Aditya Mohan Jadhav (Cogent Economics & Finance, 2019)
This paper examines the advancement of literature on gender diversity on corporate boards (board gender diversity). We discuss important management theories cited in the literature and examine the factors that affect board gender diversity. We present evidence from developed and emerging markets based on a review of studies to show how board gender diversity impacts a firm performance. We also review growing literature on the gender quota legislation that mandates the appointment of female director(s) on corporate boards. Research on board gender diversity reveals director characteristics, firm size, board size, board diversity, industry, type of ownership, customer base, and social and cultural characteristics as the factors that influence representation of female directors on corporate boards. Studies on the impact of board gender diversity on firm performance present inconclusive results. In a similar vein, studies on the impact of gender quota legislation on firm performance also present mixed results. Our study contributes to the growing literature on board gender diversity and provides a further understanding of factors that influence gender diversity on corporate boards. It also offers insights to regulators on potential limitations and the benefits of gender quota legislation.
Keywords: 330; Board gender diversity; gender quota; female directors